Operating OpenShift : an SRE approach to managing infrastructure - Rackow, Rick (O'Reilly Media, 2022)
Kubernetes has gained significant popularity over the past few years, with OpenShift as one of its most mature and prominent distributions. But while OpenShift provides several layers of abstraction over vanilla Kubernetes, this software can quickly become overwhelming because of its rich feature set and functionality. This practical book helps you understand and manage OpenShift clusters from minimal deployment to large multicluster installations. Principal site reliability engineers Rick Rackow and Manuel Dewald, who worked together on Red Hat's managed OpenShift offering for years, provide valuable advice to help your teams operate OpenShift clusters efficiently. Designed for SREs, system administrators, DevOps engineers, and cloud architects, Operating OpenShift encourages consistent and easy container orchestration and helps reduce the effort of deploying a Kubernetes platform. You'll learn why OpenShift has become highly attractive to enterprises large and small. Learn OpenShift core concepts and deployment strategies Explore multicluster OpenShift Container Platform deployments Administer OpenShift clusters following best practices Learn best practices for deploying workloads to OpenShift Monitor OpenShift clusters through state-of-the-art concepts.